Exploring the Efficacy of Intravenous Tramadol and Dexmedetomidine for Preventing Post-Anesthesia Shivering: A Year-long Randomized Clinical Trial - Kalyantshetti, Nikhita; Aisha, Shaik; Shivapujimath, Manjunath; Mahantshetti, Prakash (Journal of Neonatal Surgery, 2025)
Background and aim: Regional anesthesia is a widely used procedure for various surgical procedures However, it can lead to undesirable effects such as hypotension, bradycardia, and shivering. The aim of this research was to investigate the effectiveness, hemodynamic impacts, and potential adverse reactions associated with the administration of dexmedetomidine and tramadol in the management of post-anesthesia shivering. Materials and Methods: A randomized study was carried out involving 60 patients, who were categorized into two groups: Group-T and Group-D. These groups comprised individuals of both genders with ASA Grades 1 and 2, aged between 18 and 50 years, and scheduled for various surgical procedures under general anesthesia. In each group, 30 patients were administered an intravenous bolus of dexmedetomidine (50 mcg) and tramadol (50 mg). The study observed the grade of shivering, onset of shivering, recurrence, response rate, and adverse effects at designated intervals. Data analysis was performed using an unpaired t-test. Results: Injection Tramadol and injection Dexmedetomidine was nearly equally effective at preventing post-anesthesia shivering. Dexmedetomidine provided better pain management and a lower incidence of nausea and vomiting than tramadol, however it was related with bradycardia and hypotension. Conclusion: We find that, although both medications prove to be efficacious, the duration needed to alleviate shivering was practically the same for both dexmedetomidine and tramadol. Also, dexmedetomidine has little side effects, but tramadol causes considerable nausea and vomiting